Electrical stimulation of somatic human stem cells mediated by composite containing conductive nanofibers for ligament regeneration. (March 2017) - Dodel, Masumeh; Hemmati Nejad, Nahid; Bahrami, S. Hajir; Soleimani, Masoud; Mohammadi Amirabad, Leila; Hanaee-Ahvaz, Hana; Atashi, Amir
Abstract: One of the advances in the field of biomedical nanotechnology, is conductive nanofiber fabrication and the discovery of its applications. Biocompatible flexible nanofibers that have a good biocompatibility, mechanical properties and morphology. Poly (3, 4-ethylene dioxythiophene) (PEDOT) is a conductive polymer that has recently been used in medical applications. In this study, the electrospinning technique and vapor phase polymerization combination method with freeze drying was used to produce Silk fibroin/PEDOT/Chitosan nanocomposite scaffold. The aim of our study was to develop a ligament construct of PEDOT/Silk bilayer nanofibrous scaffold, to mimic the aligned collagen fiber bundles and Chitosan sponge coating was done on these fibrous scaffolds, to mimic the glycosaminoglycans of ECM sheath. The developed constructs were characterized. The unrestricted somatic human stem cells (USSC), were cultured on the scaffold. Then, the effect of applying DC electric pulses to cells cultured on polymer was assessed. Cellular function was actively exhibited in scaffold with electrical induction, as evident by the high expression of collagen I, collagen III, decorin, biglycan and aggrecan genes. Novel scaffold plus electrical stimulation shows facilitating cell seeding and promoting cell proliferation, differentiation. This composites can be used in this new field for stem cells differentiation to target tissues. Graphical abstract: Highlights: Layered PEDOT-Silk-Chitosan nanocomposite construct was developed. Electrical stimulation increase stem cells growth and proliferation on PEDOT nanofibers containing mat. Electrical stimulation increase the ligament related gene expression on PEDOT nanofibers containing mat. The developed nanocomposite construct would be suitable for ligament regeneration.